2005
DOI: 10.1097/01.mib.0000192325.28168.08
|View full text |Cite
|
Sign up to set email alerts
|

Bone Loss in Crohnʼs Disease: Exercise As a Potential Countermeasure

Abstract: Crohn's disease (CD) is associated with a number of secondary conditions including osteoporosis, which increases the risk of bone fracture. The cause of metabolic bone disease in this population is believed to be multifactorial and may include the disease itself and associated inflammation, high-dose corticosteroid use, weight loss and malabsorption, a lack of exercise and physical activity, and an underlying genetic predisposition to bone loss. Reduced bone mineral density has been reported in between 5% to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 95 publications
0
21
0
1
Order By: Relevance
“…Exercise may improve skeletal health and has been shown to improve bone mineral density in patients with IBD. 12 Many patients with CD have some degree of bone loss 44 and are at increased risk to develop fracture. 45 Physical activity has been shown to decrease the risk of colon cancer 13 and this association might have implications in the IBD population already at increased risk for colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise may improve skeletal health and has been shown to improve bone mineral density in patients with IBD. 12 Many patients with CD have some degree of bone loss 44 and are at increased risk to develop fracture. 45 Physical activity has been shown to decrease the risk of colon cancer 13 and this association might have implications in the IBD population already at increased risk for colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ankylosing spondylitis has been specifically associated with IBD, but the exercise therapy improved the flexibility strength and reduced pain of the joints [120]. IBD is associated with decreased bone mineral density and increased risk of osteoporosis [121] and preventive role of exercise has been proposed [122124]. It was demonstrated that physical exercise can increase bone mineral density (BMD) in CD and may reduce the risk of osteoporotic fracture [122].…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the anti-inflammatory effect both APN [30] and moderate intensity exercise by reducing the oxidative tissue damage [27] and increasing the activity of free radical scavengers [31]. However, few contradictory conclusions had been drawn regarding the effects of exercise on ulcerative colitis [32] and hence the effects of exercise remain unclear [33]. The clinical and the histological observations were further supported by the secreted cytokine studies.…”
Section: Discussionmentioning
confidence: 99%